Penerapan Instruksi pada Tahap Orientasi Pembelajaran Guided Inqury untuk Meningkatkan Kemampuan Menemukan dan Menghubungkan Konsep - Nurul Hidayati; Sri Widoretno; Nurmiyati Nurmiyati (Universitas Sebelas Maret, 2017)
This study aim to improve student’s discovering and relating ability by applying instruction of orientation stagein guided inquiry learning. The design of this research was class action research which colaborated with teacher.The research methode was applying by action, planning, observing, and reflection. The subject of research were11 boy students and 23 girl students from Senior High School. The data collecting was done by observingstudent’s activity in the class, interviewing, taking picture and tes t methode for measuring concept map scorebased on expert concept map. The data was presented in concept map, notes, and studen’s answer as thediscovering and relating indicators concept.Validity test using triangulation data, which analyzing by datareduction, data display, and conclusion drawing. Result of the research was score range of concept map whichwere 3,09% - 27,58% in pracycle; 8,81% - 62,47% in first cycle, and 10,9% - 68,5% in second cycle. Conceptmap score based on expert concept map in pracycle, first cycle, and second cycle was 16%; 29,9%; and 43,1%.Based on the resu;t, concept map score in every cycle was improving. So we can conclude from the researchthat by implementation instuction of orientation stage in guided inquiry learning was improved student’s abilityto discovering and relating concept.